Towards multimodal interactions in the multilingual EFL classroom: Lessons from a COIL experience - Pouromid, Sajjad (Indonesian Journal of Applied Linguistics, 2019)
Internationalization of higher education has recently gained momentum, and many tertiary education institutions have felt it incumbent upon themselves to foster this trend. Due to lack of resources, student and faculty mobility has not always been a viable option, however. Thus, as an alternative to Internationalization Abroad, Internationalization at Home has gained popularity. Empowering learners by making them interculturally competent is one of the main concerns in this trend. Foreign language education within a curriculum that emphasizes intercultural interaction can, therefore, play significant roles in realizing the internationalization agenda. The present study was therefore designed to explore the nature of such intercultural interactions from a conversation analytic view. It builds upon data collected from audiovisual intercultural exchanges of 16 Japanese and 18 Taiwanese students engaged in a Collaborative Online International Learning (COIL) program between a Japanese university and a university from Taiwan. The data is used to shed light on the less explored potentials of COIL in bringing together EFL classes from across borders and giving learners the opportunity to engage in intercultural interactions in a virtual multilingual context. The conversation analysis of the video recorded interactions of the learners indicates how they use a variety of multimodal resources to maintain intersubjectivity with their peers from a different cultural background when they evaluate their English proficiency as inadequate. The results also suggest that multimodal and translingual practices frequently occur in classes where learners do not share an L1 and therefore have to be systematically attended to.